Survey on mixed impulse and Gaussian denoising filters. Issue 16 (23rd February 2021) - Mafi, Mehdi; Izquierdo, Walter; Cabrerizo, Mercedes; Barreto, Armando; Andrian, Jean; David Rishe, Naphtali; Adjouadi, Malek
Abstract : This study presents a comprehensive survey on mixed impulse and Gaussian denoising filters which are applied to an image in order to gauge the effects of this type of noise combination and to then determine optimal ways that can overcome such effects. The random noise model considered in this survey is the combined effect of impulse (salt and pepper) and Gaussian noise. After describing the noise models, the denoising filters which are applied to the images are classified and explained according to their design structure, the type of filters they use, the noise level they could overcome, and the limitations they face. This survey covers all related denoising methods and provides an assessment of the strengths and practical limitations of the different classes of denoising filters.